Stilistika Genetik dalam Novel Sang Keris Karya Panji Sukma dan Pemanfaatannya Sebagai Materi Pembelajaran Apresiasi Sastra di SMA - Hanan Lestari (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The beauty of literary works can be examined through the language employed by the author using a stylistic approach. Stylistics, particularly genetic stylistics, views the author's personal characteristics, known as genetic stylistics. This research examines genetic stylistics in the novel “Sang Keris” by Panji Sukma and its utilization as teaching material for literature appreciation in high schools. The objectives of this study are to describe the use of diction, imagery, and discourse as expressions of Panji Sukma's ideas in the novel “Sang Keris” the ideological background as a characteristic of Panji Sukma's authorial style in the novel, and the results of genetic stylistics research in the novel “Sang Keris” by Panji Sukma used as teaching material for literature appreciation in high schools. The research design employs descriptive qualitative methods with a genetic stylistic approach, building upon previous studies. The results indicate that Javanese and Arabic language diction are used by Panji Sukma as expressions with connotative and concrete meanings to develop the storyline. The imagery of movement, visual imagery, and auditory imagery are used by Panji Sukma to stimulate readers' imagination in concretizing characters and atmospheres in the story. Cultural and romantic discourse is employed by Panji Sukma as an expression of the characteristic features of the novel “Sang Keris” Panji Sukma's authorial style in “Sang Keris” reflects traditionalism, marhaenism, and patriotism ideologies. The findings of this research can be used as teaching material for literature appreciation in twelfth-grade high school classes.
Reuploud file repositori 28 Januari 2026_Yudi
Keywords: Sang Keris; stylistic; discourse; ideology